Research-Based Islamic Education Curriculum Reformulation:Epistemological Reconstruction, Design, Implementation, and the Role of Teachers and Lecturers in Contemporary Islamic Education - Riri Susanti; Muhammad Zuhri; Junaidi; Abdur Rahman; Herina Yanti (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2026)
The current crisis in the relevance of Islamic religious education is no longer solely related to the issue of student morality, but also concerns the curriculum's ability to respond to social change, scientific developments, and the transformation of digital technology. This article aims to analyze the urgency of research-based reformulation of the Islamic Religious Education (PAI) curriculum as a new paradigm for Islamic education that is more reflective, critical, and adaptive. The research uses a qualitative approach with a critical literature study design. The results show that the conventional PAI curriculum is still predominantly normative-doctrinal in nature and has not fully developed an inquiry-based academic culture. Research-based curriculum reformulation allows for the simultaneous integration of revelation, rationality, social experience, and educational technology. Teachers and lecturers are no longer positioned as transmitters of knowledge, but as intellectual facilitators and producers of Islamic educational knowledge. This article emphasizes that research-based transformation of the PAI curriculum is a strategic necessity in building contextual, humanistic, and future-oriented Islamic education.